A universal anti‐Xa assay for rivaroxaban, apixaban, and edoxaban measurements: method validation, diagnostic accuracy and external validation. (6th May 2021) - Willekens, Guido; Studt, Jan‐Dirk; Mendez, Adriana; Alberio, Lorenzo; Fontana, Pierre; Wuillemin, Walter A.; Schmidt, Adrian; Graf, Lukas; Gerber, Bernhard; Bovet, Cedric; Sauter, Thomas C.; Nagler, Michael
Summary: A universal anti‐Xa assay for the determination of rivaroxaban, apixaban and edoxaban drug concentrations would simplify laboratory procedures and facilitate widespread implementation. Following two pilot studies analysing spiked samples and material from 698 patients, we conducted a prospective multicentre cross‐sectional study, including 867 patients treated with rivaroxaban, apixaban or edoxaban in clinical practice to comprehensively evaluate a simple, readily available anti‐Xa assay that would accurately measure drug concentrations and correctly predict relevant levels in clinical practice. Anti‐Xa activity was measured by an assay calibrated with low‐molecular‐weight heparin (LMWH) in addition to ultra‐high performance liquid chromatography‐tandem mass spectrometry (LC‐MS/MS). As an external validation, LMWH‐calibrated anti‐Xa activity was also determined in nine external laboratories. The LMWH‐calibrated anti‐Xa activity correlated strongly with rivaroxaban, apixaban or edoxaban drug levels [ r s = 0·98, 95% confidence interval (CI) 0·98–0·98]. The sensitivity for the clinically relevant cut‐off levels of 30, 50 and 100 µg/l was 96·2% (95% CI 94·4–97·4), 96·4% (95% CI 94·4–97·7) and 96·7% (95% CI 94·3–98·1) respectively. Concordant results were obtained in the external validation study. In conclusion, a universal, LMWH‐calibrated anti‐Xa assay accurately measured rivaroxaban, apixaban and edoxaban concentrations and correctly predicted relevant drug concentrations in clinical practice.